Otimização de dieta referência para jundiá (Rhamdia quelen) - Corrêia, Viviani (2013)
The study aimed to improve semipurified diets through the evaluation of different protein and glycidic sources as well as their combinations, taking into account performance and metabolism parameters. Three feeding were conducted which lasted 40 days trials in a water re-used system. In the first experiment different combinations of protein sources were evaluated: casein + fish meal, albumin + casein, fish meal + albumin, fish meal + casein + albumin and gelatin + casein. The fish which were submitted to the treatment casein + fish meal had higher weight, specific growth rate (SGR), daily weight (DWG), weight gain ratio (RWG), feed efficiency (FE), protein efficiency ratio (PER), retention coefficient protein, protein deposition and body fat, and better feed conversion rate (FCR). The animals subjected to casein + fish meal showed lower hepatosomatic index than fish treated with gelatin + casein, and less abdominal fat index than those fed with fish meal + albumin. In the second experiment, different carbohydrate sources were tested: corn starch, fructose, maltodextrin and sucrose. The animals which were submitted to the maltodextrin treatment showed the highest activity of acid protease and chymotrypsin activity greater than those fed with fructose, and even higher trypsin activity than those treated with corn starch. The concentration of triglyceride in plasma was higher in animals submitted to the maltodextrin treatment than in those undergoing corn starch and sucrose. The fish in the corn starch treatment also exhibited the highest body protein deposition, higher retention coefficient protein than animals treated with sucrose and frutose, and lower composition and body fat deposition than animals fed with maltodextrin. In the third experiment examined, different combinations of protein sources and glycidic were tested: casein + corn starch, casein + fructose, fish meal + corn starch, fish meal + fructose and gelatin + casein + maltodextrin. The fish which were submitted to the treatment fish meal + corn starch showed higher weight than SGR, DWG and RWG. FCR better was also detected and there was larger FE and PER in the animals fed with fish meal + corn starch and fish meal + fructose. The highest deposition of protein and fat and the highest retention coefficient protein were found in fish treated with fish meal + corn starch. The concentration of circulating glucose was higher in fish submitted to fish meal + corn starch, and plasma levels of total protein and free amino acids were higher in the fed with fish meal + corn starch compared to fish fed fish meal + fructose and casein + fructose. The conclusion is that combinations of casein + fish meal + maltodextrin or fish meal + casein + corn starch or fish meal + corn starch can be used in studies on the nutritional requirements for jundiá juveniles, as they provide adequate metabolic dynamic efficiency and zootechnical for animals.